A Case of Herpes Simplex Virus Encephalitis Without Pleocytosis in Cerebrospinal Fluid and Complicated With Intracranial Hematoma - Sagmak-Tartar, Ayse; Ozer-Balin, Safak; Akbulut, Ayhan; Gonen, Murat; Demirdag, Kutbeddin (Aves, 2020)
[Abstract Not Available]
Beyin-omurilik sıvısında pleositoz saptanmayan ve ıntrakraniyal hematomla komplike olan bir herpes simpleks virusu ensefaliti olgusu